A mysterious clavicular swelling - Nur Saadah Mohamad (Academy of Family Physicians of Malaysia, 2021)
The clavicle or collarbone is a horizontal-axis bony structure located between the neck and thoracic area. Tumour metastasis at the clavicle is very rare. Due to its location at the border of the neck and chest area, a primary tumour could originate from both areas. We report the case of a 39-year-old man who presented with a painful right sternal-end clavicular mass and intermittent fever. Chest radiography was normal. Musculoskeletal ultrasound of the clavicle revealed a mass. Computed tomography (CT) thorax further identified a mass at the upper lobe of the right lung. CT-guided tissue biopsy confirmed that it was a lung adenocarcinoma. This case shows an atypical presentation of lung carcinoma and how musculoskeletal ultrasound helped in the diagnosis when other features and investigations were inconclusive.